ANALYSIS OF DETERMINANTS THAT INFLUENCE THE VOLUME OF INDONESIAN SEAWEED EXPORTS TO MAIN DESTINATION COUNTRIES IN 2012 – 2022 - Hidayatul Rizka Devi; Putu Krisna Adwitya Sanjaya (Adisam Publisher, 2024)
Seaweed is one of Indonesia's top marine and fishery commodities, with a significant amount of untapped potential. Despite the fact that seaweed is currently a highly valuable commodity, this potential has not been fully realized.The state of Indonesia's seaweed exports is prone to fluctuations, so it's critical to monitor these issues in order to identify the factors that drive increases and decreases in the amount of seaweed exported from Indonesia to destination nations. The purpose of this study is to examine the factors that simultaneously affect the amount of Indonesian seaweed exported to the major destination nations in 2012–2022, including population size, GDP per capita, inflation, and currency rates.